Opsiini leafhopper genus Libengaia Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae) in Africa and India with description of one new subgenus and six new species - Viraktamath, C.a.; Webb, M. D.; Yeshwanth, H.m. (Zootaxa, 2024)
The genus Libengaia Linnavuori is redescribed along with one new subgenus Libengaia (Nandiana) subgen. nov. (type species: Litura bharatiensis Malhotra & Sharma) and one new species, L. (Nandiana) ramamurthyi sp. nov. (India: Jarkhand). In addition, five new species of the genus from West Africa, L. (Libengaia) brevistylus sp. nov. (Cameroon), L. (L.) deemingi sp. nov. (Nigeria), L. (L.) immaculata sp. nov. (Cameroon), L. (L.) longistylus sp. nov. (Cameroon) and L. (L) trifida sp. nov. (Nigeria) are described and illustrated. Cestius terminaliae Viraktamath syn. nov. is treated as a junior synonym of Libengaia (Nandiana) bharatiensis (Malhotra & Sharma). L. (L.) deemingi breeds on Terminalia avicennioides Guill. & Perr. and is attended by an ant (Hymenoptera: Formicidae). L. (N.) bharatiensis also breeds on Terminalia arjuna (Roxb., Wight & Arn.) (Conbretaceae) and shows considerable colour variation.